"Are you so ashamed to come from Poland and to speak your mother tongue?"- metalinguistic talk, identities and language ideologies in teenagers’ interactions on ASKfm - Obojska, Maria Antonina (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
This article applies the concept of metasociolinguistic stance specifically to investigate and analyse how identities and competing discourses can be (re)constructed in metalinguistic talk. In particular, the article analyses how stancetaking can serve as a vessel for constructing language ideologies and identities in metalinguistic talk between a Polish teenager based in Norway and her followers on a social media platform. Inspired by online ethnography, this study combines the observation of online activities, the analysis of screendata, as well as data obtained through direct online and offline discussions with the profile owner. The study showed that the focal participant and her predominantly Polish followers took different metasociolinguistic stances towards the use of Polish and Norwegian in communication between people of Polish origin. While the homeland-based followers constructed an indexical link between ethnic origins and obligatory practice of speaking Polish, the focal participant contested these ideological assumptions and oriented towards a more flexible understanding of the relationship between language and belonging. This contribution shows how social media can serve as a rich research site where the members of diasporic communities and the members of the homeland societies come into contact and interact with each other bringing in different discourses and ideologies into the conversations.